2021
DOI: 10.15421/192106
|View full text |Cite
|
Sign up to set email alerts
|

How Human Decision-making Biases Influence Health Outcomes in Patient Care

Abstract: Purpose: Medical treatments and medical decision making are mostly human based and therefore in risk of being influenced by cognitive biases. The potential impact could lead to bad medical outcome, unnecessary harm or even death. The aim of this comprehensive literature study is to analyse the evidence whether healthcare professionals are biased, which biases are most relevant in medicine and how these biases may be reduced. Approach/Findings: The results of the comprehensive literature based meta-analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Calculations of formula (1) showed that the efficiency of Group 2 compared to Group 1 is 23.80% higher, which in turn confirms the appropriateness of implementing and using medical mobile applications by physicians in outpatient appointments.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Calculations of formula (1) showed that the efficiency of Group 2 compared to Group 1 is 23.80% higher, which in turn confirms the appropriateness of implementing and using medical mobile applications by physicians in outpatient appointments.…”
Section: Resultsmentioning
confidence: 66%
“…Research on the use of mobile applications in medicine and medical education is limited and closely related to the mobile health concept (mHealth). Maintaining a work-life balance for physicians requires learning to increase efficiency and effectively manage the limited resource of available time [1]. The physicians serve increasingly complex patients in less time, deal with more administrative paperwork, and are more easily accessible through e-mail, pagers, cell phones, and other technological tools, which contributes to high burnout rates [2].…”
Section: Literature Reviewmentioning
confidence: 99%